2021
DOI: 10.3390/children8050358
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events of Mind-Body Interventions in Children: A Systematic Review

Abstract: Mind-body interventions (MBIs) are one of the top ten complementary approaches utilized in pediatrics, but there is limited knowledge on associated adverse events (AE). The objective of this review was to systematically review AEs reported in association with MBIs in children. In this systematic review the electronic databases MEDLINE, Embase, CINAHL, CDSR, and CCRCT were searched from inception to August 2018. We included primary studies on participants ≤ 21 years of age that used an MBI. Experimental studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Until then, both HT and SMT can be offered to patients. HT is a very safe treatment without severe side effects, 47 and, in our experience, children usually enjoy it. Moreover, children can learn to practice it themselves, providing them with skills to gain more control over their health without using pills.…”
Section: Discussionmentioning
confidence: 64%
“…Until then, both HT and SMT can be offered to patients. HT is a very safe treatment without severe side effects, 47 and, in our experience, children usually enjoy it. Moreover, children can learn to practice it themselves, providing them with skills to gain more control over their health without using pills.…”
Section: Discussionmentioning
confidence: 64%
“…They enjoy listening to the exercises and creating their own stories with their vivid imagination. Side effects are infrequent during hypnosis (8). Sometimes, dizziness is reported, which can be prevented by lying down during the hypnosis sessions.…”
Section: What Is Hypnotherapy?mentioning
confidence: 99%
“…Sometimes, dizziness is reported, which can be prevented by lying down during the hypnosis sessions. In case reports, other adverse events like increased anxiety, dissociated states, depersonalization phenomena, physical discomfort, and retroactive amnesia have been described, but they are rare (8).…”
Section: What Is Hypnotherapy?mentioning
confidence: 99%
“…Limited trials report side effects or adverse events, but some rare, mild to moderate adverse events have been reported. 23 Indeed, hypnotherapy should always be performed by a trained professional. 24 25 Research in children and adolescents has found that hypnotherapy significantly reduces abdominal pain and symptom scores.…”
Section: Introductionmentioning
confidence: 99%
“…Hypnotherapy is generally considered safe. Limited trials report side effects or adverse events, but some rare, mild to moderate adverse events have been reported 23. Indeed, hypnotherapy should always be performed by a trained professional 24 25.…”
Section: Introductionmentioning
confidence: 99%